The effect of tracking students by ability into different schools: a natural experiment - Nina Guyon; Eric Maurin; Sandra McNally (Fondazione Eni Enrico Mattei (FEEM), 2010)
The tracking of pupils by ability into elite and non-elite schools represents a controversial policy in many countries. There is no consensus on how large the elite track should be and little agreement on the effects of any further increase in its size. This paper presents a natural experiment where the increase in the size of the elite track was followed by a significant improvement in average educational outcomes. This experiment provides a rare opportunity to isolate the overall effect of allowing entry to the elite track for a group that was previously only at the margin of being admitted.
Keywords: I2; 330; Education; Tracking; Selection